THE CONTRIBUTION OF ADAPTED PHYSICAL AND SPORTS ACTIVITIES AND THEIR ROLE IN THE SOCIAL INCLUSION OF A SAMPLE OF PERSONS WITH DISABILITIES (DEAF–MUTE GROUP) WITHIN SOCIETY ALONGSIDE THEIR HEALTHY PEERS - Abdelaziz Chenati; Abdelghani Dogha; Yassine Derragui; Mohamede Cherif Benthabet; Kamel Nettah (International Journal of Innovative Technologies in Social Science, 2025)
The present study aimed to determine the level of social inclusion among a sample of persons with disabilities (the deaf–mute group) who practice adapted physical and sports activities alongside their healthy peers within society. We also sought to examine the statistical significance of differences across participants in terms of age and sex. To achieve these objectives, the researcher employed a descriptive research design. Data were collectedvia a final 19-item questionnaire to measure inclusion, which was administered to a sample of 43 participants and was distributed by sex and age. After appropriate statistical procedureswere applied, the study revealed that participants' inclusion was moderate. The findings further indicated that there were no statistically significant differences among participants attributable to sex or age.